Bond strength to dentin of total-etch and self-etch adhesive systems - SANTOS,Ricardo Alves dos (2014)
OBJECTIVE: To assess the bond strength to dentin of the Single Bond (3M ESPE) and XP Bond (Dentsply) total-etch and Adper SE Plus (3M ESPE) self-etch adhesive systems. METHODS: Fifteen healthy human third molars were randomly allocated across three different groups of five teeth each according to the adhesive system. The occlusal portion of each tooth was removed under refrigeration using a flexible diamond disc (EXTEC, Enfield, CT, USA) down to an area of dentin that did not reveal enamel, as confirmed under a 40X stereo microscope (Ramsor, São Paulo, Brazil). A standardized smear layer was created with #600 grit silicon-carbide paper. The adhesive systems were applied as per manufacturer recommendations, with the exception of the Adper SE Plus system, which was triple-polymerized. Composite resin blocks (5 mm) were placed on the dentin surface. The specimens were stored in distilled water for 24 hours at 37ºC. Using a flexible diamond disc (EXTEC, Enfield, CT, USA), toothpick-like specimens with an adhesive area of less than 1 mm² were obtained. A microtensile bond test was then carried out using a universal testing machine (KRATOS) with a crosshead speed of 0.5 mm/min. Analysis of variance (ANOVA) and Tukey's test were used for comparisons. RESULTS: The bond strength values obtained with each adhesive system were as follows: XP Bond, 96.24 MPa; Adper Single Bond, 72.39 MPa; Adper SE Plus, 49.91 MPa. CONCLUSION: In terms of bond strength to dentin, conventional adhesives outperform self-etching systems.